Effects of Different Sowing Dates on Growth of Different Lentil Varieties - Mandi, Gaban; Sarkar, N. C.; Palai, Jnana Bharati (International Journal of Economic Plants, 2015)
The experiment was conducted at agricultural farm of Palli Siksha Bhavana, Visva-Bharati at Sriniketan of Birbhum district,West Bengal during rabi season of 2014-15 in red and lateritic soil to study the effects of different sowing dates on growth of different lentil varieties. The soil at experimental site was analysed sandy loam in texture with low in available n, medium in available p2o5 and k2o and slightly acidic (pH: 5.79) in nature. The experiment consisted of three levels of sowing dates (i.e. 31st October, 15th November and 30th November) and four levels of lentil varieties (i.e. L 4710, RKL 607-1, PL 406 and KLS 218) thus making twelve treatment combinations which were replicated thrice and was laid out in factorial randomized block design. Growth attributes like the number of days to 50% germination, 50% flowering, pod ignition, plant height, plant dry matter accumulation were recorded. Among the extra early varieties, the optimum date for RKL-607-1 was 31st October whereas l 4710 may be sown any time of the given dates 31st October, 15th November and 30th November. The traditional variety PL 406performed best, however it was statistically at par with KLS -218.